“Scientists for a day” a program to encourage young people to science - Marín, Gustavo Horacio (2015)
In Latin America number of people choosing science and technology (S&T) as a job severely decreased. To solve this problem we launched a program that shows young students, “life models” to be followed in order to encourage them to remain in the educational system and study careers related to S&T. This work shows the results of the experience. Methods: study: descriptive, analytic with an intervention stage; unit of analysis: young students aged 12-15. Period of analysis: August 2012 to July 2014. Variables: Age, sex, type of school; scientific vocation (willingness to be a scientist, intention to study science, willingness to work in the science field); attitude towards science; marks for school subjects. Intervention consists in all day long interaction of student/researcher, in the research schedule programmed. Results: 6750 students (5.78% of 12 years old the students and 18.5% of those considered at risk of dropping out school), were included in the program. 96.8% of them felt that the experience was highly positive; 89.7% still remember the experience after 3 months as a factor that had a positive impact on your training; and 68.9% showed an increased interest and a better attitude towards science-related subjects at school according to their science teachers. 93.2% of researchers considered that the activity brought them closer to the community, 89.5% were highly pleased with activity, 72% said that after the experience they found more meaning in their research and 77.6% postulated themselves to repeat the experience. Conclusions - the program reached the goals previously set like: student motivation, increased interest in science, and social inclusion of vulnerable teenagers. Positive externalities were also seen such as increased school attendance, reduced in dropout school rate, as well as a positive assessment and high degree of satisfaction with the experience among the researchers.